2014
DOI: 10.3389/fnins.2014.00322
|View full text |Cite
|
Sign up to set email alerts
|

Combining and comparing EEG, peripheral physiology and eye-related measures for the assessment of mental workload

Abstract: While studies exist that compare different physiological variables with respect to their association with mental workload, it is still largely unclear which variables supply the best information about momentary workload of an individual and what is the benefit of combining them. We investigated workload using the n-back task, controlling for body movements and visual input. We recorded EEG, skin conductance, respiration, ECG, pupil size and eye blinks of 14 subjects. Various variables were extracted from these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
165
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(175 citation statements)
references
References 82 publications
(123 reference statements)
8
165
1
1
Order By: Relevance
“…This pleads for setting a uniform set of validated and standardized measures that covers the different levels and that is robust and sensitive to the hypothesized effects of social touch. This set could include basic physiological measures known to vary with emotional experience [e.g., heart rate variability and skin conductance; Hogervorst et al 2014]; psychological and social measures reflecting trust, proximity, togetherness, and social presence (IJsselsteijn et al 2003;Van Bel et al 2008;van Bel et al 2009), and behavioral measures, e.g., quantifying compliance and performance. Please note though that each set of measures will have its own pitfalls.…”
Section: Effect Measuresmentioning
confidence: 99%
“…This pleads for setting a uniform set of validated and standardized measures that covers the different levels and that is robust and sensitive to the hypothesized effects of social touch. This set could include basic physiological measures known to vary with emotional experience [e.g., heart rate variability and skin conductance; Hogervorst et al 2014]; psychological and social measures reflecting trust, proximity, togetherness, and social presence (IJsselsteijn et al 2003;Van Bel et al 2008;van Bel et al 2009), and behavioral measures, e.g., quantifying compliance and performance. Please note though that each set of measures will have its own pitfalls.…”
Section: Effect Measuresmentioning
confidence: 99%
“…Estimates of the EEG power in discrete frequency ranges that have known clinical significance commonly appear as input features in the brain-machine interface literature, including prior work on mental workload measurement [11][12][13][14][15][16]. As a preliminary benchmark for later comparison with more advanced processing, we evaluated the performance of a classifier that used only EEG spectral band power measurements as input features.…”
Section: A Benchmark Analysismentioning
confidence: 99%
“…Methods to measure mental workload include subjective methods using participant filled forms [6] and objective methods involving the usage of psychophysiological measurements [7]. It is found that electroencephalography (EEG) provides one of the best methods to measure mental workload, with its high temporal resolution [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that electroencephalography (EEG) provides one of the best methods to measure mental workload, with its high temporal resolution [7]. In the present study, mental workload related to multitasking activity is explored using EEG features and an algorithm for the recognition of the different levels of mental workload is proposed.…”
Section: Introductionmentioning
confidence: 99%